(untitled) (Proceedings of the International Conference on Food, Nutrition, Health and Lifestyle, 2023)
The red algae Euheuma denticulatum species (Burman) Collins at Harvey contains important elements including calcium, copper, iron, iodine, and nitrogen, chlorophyll pigments A and B, carotene, lutein, fikoeritrin, fikosinin, and polysaccharide compounds. Tempe is a food made from the fermentation of soybean seeds containing fatty acids, vitamins, minerals, antioxidants, and so forth. This study aims to produce biscuits from a combination of red algae and tempe which will be beneficial for functional food, besides that this biscuit will be tested by chemical analysis. The research method uses an experimental laboratory, the red algae of the Eucheuma denticulatum species is extracted by kinetic maceration with water solvents, the tempeh is dried and caught, after that a formulation is made in the form of biscuits, and after becoming biscuits tested for nutritional content in the form of carbohydrates, proteins, fats, crude fibers , water content, ash content, and calories. Nutrition data analysis was carried out by the one-away Anova test and followed by the LSD posthoc test. From the results of the study obtained biscuits formula 1, 2 and 3 contains (65.31%, 64.66%, 64.98% carbohydrates), (6.01%, 10.52%, 8.34% water content) (1.69%, 2.44%, 2.55% ash content), (18.90%, 18.03%, 18.10% protein), (14.10%, 14.87%, 14.35% crude fat), (1.70%, 1.72%, 1.40% crude fiber), and (4341.0 kcal.kg, 4399.5 kcal.kg, 4424.0 kcal.kg calorie). In conclusion, the formula for biscuits combination of red algae extract and tempe has a large enough calorie according to the existing biscuit standards. The contribution of this research is to produce biscuits that will be used as a functional food for people with dyslipidemia.